ฟลูออเรสเซนต์จากอนุพันธ์ 4-อะมิโน-1,8-แนฟทาลิไมด์บนโซลเจล - ธนเดช นิลเกตุ (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
Two derivatives of 4-amino-1,8-naphthalimide was successfully synthesized and their fluorescence properties were investigated as functions of pH and water content in organic solvents. The two compounds were synthesized in 49-57% yields a sequence of imide condensation and nucleophilic aromatic substitution, were different in the number of N,N-dimethyl ethylenediamine units. Their maximum absorption and emission wavelengths at 444 and 532 nm, respectively. As aqueous solutions, their emission intensities decreased a when the pH increased, and this phenomenon occur red in a reversible fashion. The pH responses of these two compounds may result from the photo-induced electron transfer process upon the protonation-deprotonation of the amine groups. In most organic solvents, the fluorescence signals of these two compounds increased along with the added amounts of water, which may involve the protonation mechanism. However, the fluorescence intensities of both compounds in tetrahydrofuran (THF) are strongest in the absence of water, and became weaker as the water content increases between 0-10%. This phenomena led to the use of these compounds for determination of water content in THF, which showed a linear relationship between fluorescence quenching ratio and water content between 0 to 1%.